Poly-Herbal Neuroprotection: Pharmacological mitigation of Ischemic Damage and BBB disruption in a rat model of tMCAO - Dewaji Gathe, Sonu; Soni, Rupesh (Journal of Neonatal Surgery, 2025)
Background Cerebral ischemia due transient middle cerebral artery occlusion (tMCAO) induced substantial neuronal injury, compromises the integrity of the Blood –Brain Barrier (BBB), and result in marked neurological impairments. The present study evaluates the neuroprotective potential of a poly-herbal mixture in mitigating ischemic brain injury and promoting functional recovery. Methods A well-established tMCAO model was employed in rats to induce focal cerebral ischemia. Experimental groups included healthy controls, untreated tMCAO animals, and tMCAO animals treated with the poly-herbal mixture. Infarct volume was quantified, BBB integrity assessed via Evans blue dye extravasation, and neurological function evaluated through multiple behavioural parameters including grid hold test, limb symmetry, forepaw outstretching, body proprioception, and vibrissae touch response. Results The tMCAO group exhibited a significant increase in infarct volume (27.79 ± 3.37%) associated to healthy controls (0.00 ± 0.00%, p < 0.001). Treatment with the poly-herbal mixture significantly reduced infarct volume (6.15 ± 3.70%, p < 0.01), with no statistically significant difference from healthy controls. BBB disruption in the tMCAO group was confirmed by elevated Evans blue dye concentration (7.93 ± 0.67), while treated animals showed significantly reduced levels (3.55 ± 0.37, p < 0.0001), indicating partial restoration of BBB integrity. Neurological scores significantly improved with treatment across all behavioural parameters. Grid hold test scores increased from 0.61 ± 0.25 (tMCAO) to 2.11 ± 0.17 (treated group). Improvements were similarly observed in limb symmetry (2.17 ± 0.18), forepaw outstretching (2.33 ± 0.44), body proprioception (2.39 ± 0.23), and response to vibrissae touch (2.66 ± 0.23), all with p < 0.0001. Conclusion The poly-herbal mixture demonstrated robust neuroprotective effects in the tMCAO model by significantly reducing infarct volume, partially restoring BBB integrity, and improving motor and sensory functions. These findings support the therapeutic potential of poly-herbal strategies for ischemic stroke and warrant further investigation.